The Role of Kisspeptin in Sexual Behavior - Hellier, Vincent; Brock, Olivier; Bakker, Julie (Seminars in Reproductive Medicine, 2019)
Sexual behavior is essential for the perpetuation of a species. In female rodents, mate preference and lordosis behavior depend heavily on the integration of olfactory cues into the neuroendocrine brain, yet its underlying neural circuits are not well understood. We previously revealed that kisspeptin neurons in the anteroventral periventricular nucleus/periventricular nucleus continuum (AVPv/PeN) are activated by male olfactory cues in female mice. Here, we further reveal that male-directed mate preferences and lordosis are impaired in kisspeptin knockout mice but are rescued by a single injection with kisspeptin. Acute ablation of AVPV/PeN kisspeptin neurons in adult females impaired mate preference and lordosis behavior. Conversely, optogenetic activation of these neurons triggered lordosis behavior. Kisspeptin neurons act through classical GPR54/GnRH signaling in stimulating mate preferences, but unexpectedly, GPR54/GnRH neuronal ablation did not affect lordosis behavior. Therefore, to identify the downstream components of the neural circuit involved in lordosis behavior, we employed genetic transsynaptic tracing in combination with viral tract tracing from AVPV/PeN kisspeptin neurons. We observed that kisspeptin neurons are communicating with neurons expressing the neuronal form of nitric oxide synthase. These results suggest that hypothalamic nitric oxide signaling is an important mechanism downstream of kisspeptin neurons in the neural circuit governing lordosis behavior in female mice.
Keywords: sexual behavior; hypothalamus; olfaction; GnRH; nitric oxide